Two new species of Psolus Oken from Brazil (Holothuroidea: Psolidae), with neotype designation and redescription of Psolus vitoriae Tommasi, 1971, and a key to the southwestern Atlantic and Magellanic species - Martins, Luciana; Tavares, Marcos (Zootaxa, 2019)
The taxonomy of the southeastern Brazilian species of Psolus is reviewed and two new species described. Additionally, P. vitoriae is redescribed based on a newly designated neotype and supplemental material from the type locality and nearby regions. The synonymy of P. marcusi with P. patagonicus is called into question. The calcareous ring is useful for distinguishing between some Psolus species. Psolus tommasi sp. nov. is characterized by having five oral valves, an anus covered by a variable number of small, irregular anal valves, oral and anal valves distinct from body wall scales, calcareous ring interradial plates entire, calcareous ring simple, without posterior processes; radial and interradial plates entire, dorsal ossicles spheroid bodies and sole ossicles knobbed and smooth perforated plates. Psolus thandari sp. nov. is characterized by granules on body scales; mouth surrounded by five to seven triangular valves of equal size; anus surrounded by a variable number of small and irregular anal valves that grade into surrounding scales; calcareous ring with interradial plates entire. Six species of Psolus are known from the southwestern Atlantic and Magellanic region: P. vitoriae (São Paulo, Brazil); P. patagonicus (Mar del Plata to Tierra del Fuego, Argentina; Strait of Magellan and Cape Horn); P. segregatus (Patagonia, Argentina; Strait of Magellan, Chile; Hikurangi Margin and Chatham Rise, New Zealand); P. antarcticus (Magellanic region; South Georgia Island, southern Atlantic Ocean; Macquarie Island and Ridge, New Zealand); P. lawrencei (Mar del Plata, Argentina) and Psolus murrayi Théel, 1886 (Montevideo, Uruguay). A key to the species of Psolus from the southwestern Atlantic and Magellanic region, and a synoptic table to all southern Atlantic Psolus species is provided.